Evaluation of Methane and Carbon Dioxide Emission Decrease Through Waste Composting - Pitaratae, Apinan; Pitaksanurat, Somsak; Limsakul, Atsamon (International Journal of Environment, 2017)
The organic waste disposal under anaerobic conditions emits Methane, which causes increased global warming. This study attempts to find the emission factor in windrow waste composting systems from two sizes of gathered organic waste piles. Designed to compare two groups of composting piles, one pile consisted of 500 kilograms of waste originating from local authorities while the other amounted to 250 kilograms of waste collected from households. With six piles of each type, aeration was done by manual turning and emissions were sampled in closed flux chambers and analyzed by gas chromatographs. A control experiment, modeling landfill sites, was set up in a one x one x one meter hole. Results from the experiment showed that emission ratios from the 500 kg was 1.3613 x 10-3 g CO2-eq kg-1 wet waste, and 1.3427 x 10-3 g CO2-eq kg-1 wet waste from the 250 kg experiment. The 500 kg experiment decreased emissions by 0.059185 g CO2-eq kg-1 wet waste and the 250 kg experiment, emissions decreased by 0.059206 g CO2-eq kg-1 wet waste when compared to the control group. In summary, pile size has no effect on emission ratios. Statistical testing found no significance difference between emissions from the 500 kg compared with the 250 kg. This study tells us that massive landfill or waste composting is difference effect.INTERNATIONAL JOURNAL OF ENVIRONMENTVolume-5, Issue-4, Sep-Nov 2016, Page: 44-55